Food shopping behaviors of residents in two Bronx neighborhoods - Rachel Dannefer; Tamar Adjoian; Chantelle Brathwaite; Rhonda Walsh (AIMS Press, 2015)
Background: Numerous researchers have documented associations between neighborhood food environments and residents' diets. However, few quantitative studies have examined the food shopping behaviors of residents in low-income neighborhoods, including the types of stores patronized and frequency of visits. This study presents findings on the food shopping behaviors of residents in the Bronx neighborhoods of West Farms and Fordham. Methods: Street-intercept surveys were conducted in spring 2012 with residents of West Farms and Fordham as part of a broader program evaluation. The survey included questions on general food shopping behaviors including visits to neighborhood bodegas (corner stores) and supermarkets, mode of transportation to the supermarket most commonly frequented, and the primary source for purchases of fruits and vegetables. Results: The survey was conducted with 505 respondents. The sample was 59% Hispanic and 34% black, with a median age of 45 years. Thirty-four percent of respondents had less than a high school education, 30% were high school graduates or had their GED, and 36% had attended some college. Almost all respondents (97%) shopped at supermarkets in their neighborhood; 84% usually shopped at a supermarket within their neighborhood, and 16% usually shopped at a supermarket outside of their neighborhood. Most respondents (95%) shopped at bodegas in their neighborhood, and 65% did so once per day or more. Conclusions: Residents of these neighborhoods have high exposure to local food stores, with the vast majority of respondents shopping at neighborhood supermarkets and bodegas and almost 2 in 3 respondents going to bodegas every day. These findings demonstrate the important role of supermarkets and bodegas in local residents' shopping patterns and support the inclusion of these stores in efforts to create food environments that support and promote healthy eating.